2004
DOI: 10.1002/fld.675
|View full text |Cite
|
Sign up to set email alerts
|

Operator‐splitting method for the analysis of cavitation in liquid‐lubricated herringbone grooved journal bearings

Abstract: SUMMARYThis paper presents an operator-splitting method (OSM) for the solution of the universal Reynolds equation. Jakobsson-Floberg-Olsson (JFO) pressure conditions are used to study cavitation in liquidlubricated journal bearings. The shear ow component of the oil ÿlm is ÿrst solved by a modiÿed upwind ÿnite di erence method. The solution of the pressure gradient ow component is computed by the Galerkin ÿnite element method. Present OSM solutions for slider bearings are in good agreement with available analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…For the same operating conditions and bearing dimensions various authors have reported various values of attitude angle at the same eccentricity ratio. The difference may be because of the cavitation boundary considered, as Rao and Sawicki 12 and Jiankang et al 20 have considered non-dimensional cavitation pressure as P c = 0; and Lee et al 11 and Jang and Chang 9 have considered non-dimensional cavitation pressure are P c = −1. In the present analysis, the cavitation pressure considered is P c = 0, and the attitude angle results although not in complete agreement but are closer to Jiankang et al 20 results.…”
Section: Discussion On the Various Challenges/complexities In The Ana...mentioning
confidence: 99%
“…For the same operating conditions and bearing dimensions various authors have reported various values of attitude angle at the same eccentricity ratio. The difference may be because of the cavitation boundary considered, as Rao and Sawicki 12 and Jiankang et al 20 have considered non-dimensional cavitation pressure as P c = 0; and Lee et al 11 and Jang and Chang 9 have considered non-dimensional cavitation pressure are P c = −1. In the present analysis, the cavitation pressure considered is P c = 0, and the attitude angle results although not in complete agreement but are closer to Jiankang et al 20 results.…”
Section: Discussion On the Various Challenges/complexities In The Ana...mentioning
confidence: 99%
“…Jang and Chang (2000) analyzed the performance of a herringbone grooved journal bearing in the spindle motor of a computer hard disk drive including the effects of cavitation by using the finite volume method with mesh fitting the groove profiles. Many other references (Wu et al, 2004;Lee et al, 2004;Chao and Huang, 2005;Chen et al, 2012) also studied the lubrication performance of MHGJB by using the FDM in the non-orthogonal coordinate system with skew mesh. However, it should be pointed out that there exists some numerical singularity for the MHGJB at the critical line of two skew coordinate systems if groove fitting meshes are used, especially for the large skew angle of herringbone grooves.…”
Section: Introductionmentioning
confidence: 99%